2014
DOI: 10.1111/1756-185x.12474
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐induced diabetes mellitus in systemic lupus erythematosus patients: analysis from a Malaysian multi‐ethnic lupus cohort

Abstract: The prevalence of SDM among SLE patients was 13% and Indians were more prone to develop SDM compared to other races. Higher numbers of system involvement, abdominal obesity, hypertriglyceridemia and the use of oral prednisolone of ≥ 1 mg/kg/day were associated with SDM, while HCQ use potentially protects against SDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
(53 reference statements)
2
17
0
4
Order By: Relevance
“…We found higher baseline glucose and IFG to be associated with NODAG, consistent with similar findings in solid‐organ transplant . Hyperlipidaemia and lower HDL‐C were associated with NODAG in our cohort, as well as incident diabetes in individuals with systemic lupus erythematosus and in the general population, likely reflecting the underlying metabolic syndrome . We also found proteinuria to be associated with NODAG (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found higher baseline glucose and IFG to be associated with NODAG, consistent with similar findings in solid‐organ transplant . Hyperlipidaemia and lower HDL‐C were associated with NODAG in our cohort, as well as incident diabetes in individuals with systemic lupus erythematosus and in the general population, likely reflecting the underlying metabolic syndrome . We also found proteinuria to be associated with NODAG (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…[12][13][14] Hyperlipidaemia and lower HDL-C were associated with NODAG in our cohort, as well as incident diabetes in individuals with systemic lupus erythematosus and in the general population, likely reflecting the underlying metabolic syndrome. 15,16 We also found proteinuria to be associated with NODAG ( Fig. 1).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Antimalarial agents have been used to treat SLE in over 50 years and since 1990s, there is well-established evidence of its various benefits including anti-thrombotic, anti-hyperlipidaemic, prevention of disease flares and damage in lupus [38]. Our previous studies have also found that the use of HCQ was associated with less disease damage in a small lupus nephritis cohort [35] and was associated with less SDM complication [45]. …”
Section: Discussionmentioning
confidence: 99%